Technical and economic feasibility of improved postharvest management practices in enhancing the eggplant value chain of Bangladesh - Rahman, MA; Islam, M; Begum, MM; Arfin, S (International Journal of Agricultural Research, Innovation and Technology, 2020)
A study was carried out to evaluate the suitability and effectiveness of improved postharvest management practices (IPMP) in enhancing the eggplant (Solanum melongena L.) value chain of Bangladesh. In IPMP, sorting, grading and washing of eggplants were done, and packed them in plastic crates with or without modified atmosphere packaging (MAP). Traditional postharvest management practices (TPMP) existed in the value chain was used as control treatment. IPMP including the use of plastic crate with MAP reduced weight losses by 26.7 and 38.0% at wholesale and 2-days display at retail outlets. The total postharvest loss of eggplant handled with TPMP including packed in jute sack was 40.0%, whereas it was only 4.5% when followed IPMP. The reduction of postharvest losses of eggplants handled with IPMP amounted to 88.7%, and 100.0% fruit could be sold at retail outlets. The additional weekly gross income of a small trader by selling 1000 kg eggplant handled with IPMP comprising the plastic crates with MA packaging would be BDT 17,190 (USD 207). Int. J. Agril. Res. Innov. Tech. 9(2): 35-41, December 2019